The carbon isotopic (13C/12C) signature of sugarcane bioethanol: certifying the major source of renewable fuel from Brazil1. Issue 11 (7th June 2015) - Neves, Laura A.; Sarmanho, Gabriel F.; Cunha, Valnei S.; Daroda, Romeu J.; Aranda, Donato A. G.; Eberlin, Marcos N.; Fasciotti, Maíra
<x xml:space="preserve">Abstract</x> GC/IRMS was used to measure the carbon isotopic signature (δ13CV-PDB) of the Brazilian sugarcane bioethanol.